2013
DOI: 10.1159/000353233
|View full text |Cite
|
Sign up to set email alerts
|

Human Unrestricted Somatic Stem Cell Administration Fails to Protect Nude Mice from Cisplatin-Induced Acute Kidney Injury

Abstract: Background: Kidney failure is a debilitating disorder with limited treatment options. The kidney-protective effects of stem cells have been vastly investigated and promising results have been achieved with various sources of stem cells. However, in spite of beneficial effects on other disease models, the renoprotective potential of human cord blood-derived unrestricted somatic stem cells (USSC) has not been examined so far. Methods: In the present study, acute kidney failure was induced in female nude mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Most of the studies used labeling to check or confirm the presence of injected cells in kidneys and/or other organs (see Tables 1 and 2 ). It was reported that labeled cells (PKH26, GFP, and DIO) were mostly detected in the lungs, much less in the liver and in the kidneys [ 8 , 10 , 14 , 18 , 20 , 22 , 23 , 25 ]. Cheng et al studied biodistribution and found that one hour after iv injection of syngeneic MSCs most of the radiolabeled (or GFP labeled) cells were trapped in the lungs (62%), followed by liver (12.5%), spleen (11.4%), and kidneys (5.4%), but 7 days after injection no signs of MSCs in any organ was found [ 36 ].…”
Section: Reliability Of Tracking the Injected Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies used labeling to check or confirm the presence of injected cells in kidneys and/or other organs (see Tables 1 and 2 ). It was reported that labeled cells (PKH26, GFP, and DIO) were mostly detected in the lungs, much less in the liver and in the kidneys [ 8 , 10 , 14 , 18 , 20 , 22 , 23 , 25 ]. Cheng et al studied biodistribution and found that one hour after iv injection of syngeneic MSCs most of the radiolabeled (or GFP labeled) cells were trapped in the lungs (62%), followed by liver (12.5%), spleen (11.4%), and kidneys (5.4%), but 7 days after injection no signs of MSCs in any organ was found [ 36 ].…”
Section: Reliability Of Tracking the Injected Cellsmentioning
confidence: 99%
“…Cheng et al studied biodistribution and found that one hour after iv injection of syngeneic MSCs most of the radiolabeled (or GFP labeled) cells were trapped in the lungs (62%), followed by liver (12.5%), spleen (11.4%), and kidneys (5.4%), but 7 days after injection no signs of MSCs in any organ was found [ 36 ]. Studies using GFP labeling reported disappearance of GFP + cells in the kidney 4 days after injection [ 22 , 31 ], while studies that used PKH26 [ 12 , 33 ] or CM-Dil [ 13 ] labeling reported presence of positive cells in the kidney until the end of their study, that is, 2–4 wks. Nevertheless, the fact that injected MSCs are mostly trapped in the lungs and cleared without any engraftment in kidney raise questions regarding their pathophysiologic mechanisms, as well as possibility of their potential rejection by the host's immune system.…”
Section: Reliability Of Tracking the Injected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MSCs, beneficial effects have been reported in animals treated with hematopoietic stem cells [44], induced pluripotent stem cells [45], endothelial progenitor cells [46], and mature endothelial cells [47]. In contrast to these studies, Burger et al and others have shown that certain progenitor populations increase injury in experimental AKI, thereby highlighting the critical need for careful selection of cells to ensure safe promotion of recovery [4850].…”
Section: Reviewmentioning
confidence: 99%